Pengaruh Komitmen Pegawai Sekolah Terhadap Eektivitas Implementasi Total Quality Management (Tqm) di SMKN Se-Kota Cimahi - Syukron .; Taufani Chusnul Kurniatun; H. Abu Bakar (Universitas Pendidikan Indonesia, 2019)
Total Quality Management (TQM) is trying improvement and increasement the quality continously all persons. TQM is a inovation in managing a education which make focus in improving and increasing the quality continously which oriented to customer’satisfaction. Standard of Education and The Quality Management System ISO 9001:2008 in The Vacational School is a role and quality giudance contain minimun criteria and achievement the quality which must be finished school in operating one of education.both of them must finish consistently in order to purpose school can achieve, namely involving and enableness all school society.that thing,the observer is imterested to indentify about “Comitment Of School Society About Implementation Effectivity Total Quality Management In SMKN In Cimahi”.The purpose of obserment id is to know commitment of school society about organisation,to know implementatiom effectivity TQM and to know school society about implementation Effectivity TQM. The method that is used in the observement is the method quantative, that is located in SMKN CIMAHI, by using technic sample random sampling in sample taking. A informant as data source and tecnic data collecting that is used questionnaire and interview. And the usage programme SPSS version 21.0 and Microsoft Excel in data processing.According data processing result Weight Mean Score (WMS) find observernent in school society in SMKN CIMAHI in the position EXCELLENT in getting score 4,13 where SMKN 1 Has low score 4,08 and HIGH score SMKN 2 4,37 meanwhile SMKN 3 is 4,31 and the next about implementation Effectivity TQM in School Cimahi has WELL generally in rate score 3,97 which SMKN 1 (4,00) has high score from SMKN 2 (3,97) SMKN 3 (3,91) have low score among the other school. Meanwhile finding from normality test result that variable data X and Y distribute Normal, data processing and data analysis use parametic statistic technic. From variable corelation coefision test X and Y is gotten 0,710 and test result Signification is gotten value t-hitung 12,488 and t-tabel 1,804and coefision test result detemination is getting 50,5% it means commitment of school society inflence strongly 50,5% and signification about effectivity implementatiom TQM in SMKN CIMAHI. 49,5% is influenced other factor is included he obcerverment. The conclusion that a need consistent teachers and administration staff as school society to commite about organisation through obedience about quality operate the job according the quality guidance.